2020
DOI: 10.23958/ijirms/vol05-i01/833
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cytomegalovirus among Blood Donor in Transfusion Medicine: Study from Bangladesh

Abstract: Background: Cytomegalovirus (CMV) infection is a matter for concern among blood bank professionals and blood transfusion recipient, especially in cases of transfusion to neonates and immunocompromised patients. Objective: The aim of the study was to investigate the seroprevalence of cytomegalovirus with the purpose of determining routine CMV screening for donors. Method: A descriptive cross sectional study was carried out in the Department of Transfusion Medicine in Bangabandhu Sheikh Mujib Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The present study is supported by report carried out in a tertiary care hospital of Dhaka which also demonstrated 100% pregnant women were seropositive for anti CMV IgG antibody in their first antenatal visit, reflecting a high seroprevalence of CMV IgG in Bangladesh [26]. Another recent study in Bangladesh revealed 91% seroprevalence of CMV IgG among the blood donors [27]. Finding of this study is also consistent with a report from India where seropositivity of anti-CMV IgG was 87% in women of child bearing age [28].…”
Section: Discussionsupporting
confidence: 82%
“…The present study is supported by report carried out in a tertiary care hospital of Dhaka which also demonstrated 100% pregnant women were seropositive for anti CMV IgG antibody in their first antenatal visit, reflecting a high seroprevalence of CMV IgG in Bangladesh [26]. Another recent study in Bangladesh revealed 91% seroprevalence of CMV IgG among the blood donors [27]. Finding of this study is also consistent with a report from India where seropositivity of anti-CMV IgG was 87% in women of child bearing age [28].…”
Section: Discussionsupporting
confidence: 82%